IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI UPT SMP NEGERI 1 TAPUNG - Rahman, Abdul; Zamsiswaya, Zamsiswaya; Harun, Idris (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2024)
Learning freedom could be said as the autonomy in the education field. Educational autonomy policies were revived back in this era. Liberating educational units, teachers, and students could stimulate the emergence of new innovations. Students could learn independently and creatively, so all Indonesian students from various ethnicities and cultures could have their own different ways in learning. This research aimed at knowing the implementation of Mardeka learning curriculum on Islamic Education subject at UPT State Junior High School 1 Tapung. The problems in this research were: 1) how the implementation of Mardeka learning curriculum on Islamic education subject was, 2) what the supporting factors of the implementation of the Mardeka learning curriculum on Islamic education subject were, 3) what the obstructing factors of the implementation of the Mardeka learning curriculum on Islamic Education subject was at UPT State Junior High School 1 Tapung. The data were analyzed by using qualitative analysis, namely analysis and interpretation conducted critically, and using analytical descriptive technique, namely describing and classifying data, followed by interpretation of thoughts. The research findings showed that; first, the implementation of Maedeka learning curriculum on Islamic education subject was in good category based on several items conducted by the teachers, as manager, the school principal of UPT State Junior High School 1 Tapung has been able to improve the teachers competences in the environment and he was able to manage this educational institution, so the goals were achieved. Second, the supporting factors of the implementation of Mardeka learning curriculum on Islamic education subject at UPT State Junior High School 1 Tapung were teachers’ psychology, student intelligence, very good facilities, and infrastructure. Meanwhile, the obstructing factors of implementation of Mardeka learning curriculum were the Ministry of National Education was not regularly disseminating information to schools, and there was a lack of training organized by the government regarding the independent learning curriculum.